Tren Penelitian Konseling Islam: Sebuah Studi Bibliometrik - Winarni, Tri; Santosa, Hardi; Saputra, Wahyu Nanda Eka (Universitas Nusantara PGRI Kediri, 2024)
This research aims to identify trends in scientific publications on Islamic counseling. The research uses bibliometric analysis involving scientific publications from 1989 to 2024 in the Scopus database. The keywords we use are